Online Success as Horizon of Survival: Children and the Digital Economy in Lagos, Nigeria - Serres, Jaana (Media and communication (Lisboa), 2023)
Literature on the impact of the digital ecosystem on youth is largely grounded on Western case studies and Eurocentric in its working assumptions; yet African children and teenagers—who account for most of the continent’s population—have been early adopters of social media’s possibilities and are exposed to distinctive risks. This article shows how, in the absence of viable institutional structures for self-actualization in post-liberalization Nigeria, digital platforms turn children into central actors of economic flexibility. With transitional pathways disappearing, formal employment and traditional markers of adulthood are no longer on the horizon of African youths. Uncertainty, hustling, and extraordinary aspirations are part and parcel of their socialization process, with “survival” and “success” increasingly perceived as intertwined, requiring everyone, from the youngest age, to “perform.” From rags-to-riches stories of viral children groups to racist images and videos of children feeding China’s livestreaming boom and the meme culture across the world, commodified African childhood is projected into the flows of digital popular culture, enabled by legal and socioeconomic vulnerability and the internalization of visibility as an avenue of opportunity. Nigeria in particular, with the world’s largest population of out-of-school children on the one hand, and an internationally booming entertainment industry on the other, delineates a palpable, yet unsustainable mode of aspiration and wealth acquisition through engagement with social media. This article draws on a year-long ethnographic investigation in Lagos among (a) groups of teenage aspiring dancers seeking to “blow” online and (b) marketing professionals who use children in their commercial strategies.